High-level properties and visual experience. - Fish, William (Philosophical Studies, 2013)
The article offers the author's insights regarding the elements of visual experiences. The author gives feedback about the opinion of C. I. Lewis, C. Peacocke and J. Lyons to visual experience issues. He investigates the prospects of using phenomenological methodology which yields different answers in the hands of various theorists. He concludes that there are no reasons to think that higher-level properties do not feature in the presentational, sensory component of visual experiences.